Implementation of Discovery Method in Improving Learning Outcomes of Plural and Short Prayer Material at MI Al-Karomah - Inayati, Wida (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to evaluate the effectiveness of the application of the discovery method in improving the learning outcomes of grade 3 students of MI Al-Karomah on the material of plural and shortened prayers. The discovery method is a learning approach that encourages students to actively discover concepts and principles through the process of exploration, observation, and independent analysis. This study uses a quantitative approach with a quasi-experiment design. The sample used consisted of grade 3 students of MI Al-Karomah who were divided into two groups, namely the experimental group that applied the discovery method and the control group that used conventional learning methods. Data collection was carried out through learning outcome tests, observations, and interviews. The results showed a significant increase in the learning outcomes of students taught using the discovery method compared to the traditional method. Students in the experimental group showed a deeper understanding of the concept of plural and shortened prayers and had higher learning motivation. Thus, the discovery method has proven effective in improving students' understanding and learning outcomes in this material. The implications of this study indicate that the discovery method can be an innovative learning strategy in Islamic Religious Education, especially in teaching fiqh material.